(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
In the Bukhara oasis, the use of low-mineral groundwater for irrigation and the use of waterefficient irrigation in the care of autumn cereals with the introduction of 50 kg of hydrogel crystals per hectare, seasonal irrigation, positive changes in the growth and development of grain, seasonal irrigation 3800- 4000 m3 / ha..